PERILAKU MASYARAKAT DALAM PENGELOLAAN SAMPAH ANTARA DAERAH BINAAN DAN DAERAH TIDAK BINAAN DI KOTA SURABAYA - Isa Ma'rufi (Fakultas Kesehatan Masyarakat, Universitas Jember, 2011)
The main problem at Surabaya city is waste problem. By 2.160 ton/ day, pile of waste was produced at Surabaya, so that an effort of community based waste management are needs to be done. Type of research is an observational by comparing between assisted and unassisted areas. Sample on research is 1000 people. Analyze technique used are descriptive and analytical. The results showed that respondents in assisted areas who have committed on waste management are 66.6% (range 5.1 – 91.5%). The amount is higher than in the control/ unassisted areas, which only 4.6% respondents who did the same things (range 1.7 – 6.4%). Chi-square test result demonstrated the value of P = 0,000 which is smaller than α = 0.05. According to the result of study, it is suggested to increasing motivation about the importance of sorting and processing waste at waste point source by continuity assistance to communities about periodically waste reducing program at neighborhood, village, sub district and city levels. Keywords: behavior, waste management.